Low emissions development in large-scaled farm in China - Wang, Wei; Li, Shengli (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
"Low emissions development in large-scaled farm in China" was presented by Dr. Wei Wang and Prof. Shengli Li at the Kick-off meeting on "Piloting and scaling of low emission development options in large scale dairy farms in China" on September 28th, 2020.